Analisis Efektivitas Aplikasi Write it Japanese dalam Meningkatkan Kemampuan Menulis Hiragana dan Katakana bagi Pemula - Cindy Valencia; Apik Banyubasa; Hassan Narallah Matauq; R Bramaditya Ario Wirawisesa; Humannisa Rubina Lestari (Universitas Palangka Raya, 2025)
This study aims to analyze the effectiveness of the Write it! Japanese application in improving the ability to write Hiragana and Katakana characters among beginners. The research involved 20 participants with no prior experience in learning Japanese. A pre-test and post-test design was employed, in which participants were asked to write 20 Hiragana and 20 Katakana characters before and after using the application independently for seven consecutive days, for 15 minutes per day. The results showed a significant increase in the average score from 45.05% (pre-test) to 79.05% (post-test), with an average improvement of 34%. The findings indicate that the Write it! Japanese application is effective in facilitating the learning process through stroke order animations, interactive writing practice, and gamified features that enhance motivation. Additionally, the application supports self-directed learning and serves as an efficient and engaging alternative medium for language acquisition. These findings reinforce the importance of integrating technology into foreign language education, particularly in the early stages of learning Japanese kana.